Artery of Percheron occlusion with first-pass recanalisation of the first segment of posterior cerebral artery. Issue 4 (21st April 2021) - Elsayed, Sherif; Al Balushi, Ali; Schupper, Alexander; Shoirah, Hazem
Abstract : This is an elderly patient who was found unconscious at home. CT of the head without contrast was unremarkable, while CT angiography of the head and neck revealed a subocclusive thrombus on the precommunicating (P1) segment of the left posterior cerebral artery (PCA). MRI brain revealed bilateral regions of diffusion restriction in the paramedian thalami and bilateral medial mesencephalon. Initial angiography confirmed the presence of a subocclusive thrombus in the P1 segment of the left PCA. Thrombectomy was performed achieving recanalisation of the left PCA and reperfusion of bilateral thalami via a visualised artery of Percheron. Postoperatively, the patient was kept on a daily dose of 325 mg of aspirin. The patient did not improve neurologically. A follow-up MRI brain showed diffusion restriction in the left occipital lobe and petechial haemorrhages in the bilateral thalami. The family eventually opted for palliative measures, and the patient expired on day 14 of admission due to acute respiratory failure from palliative extubating.